Surfing-Related Craniofacial Injuries: A NEISS Database Study. Issue 8 (21st November 2022) - Muhonen, Ethan G.; Kafle, Samipya; Torabi, Sina J.; Abello, Eric H.; Bitner, Benjamin F.; Pham, Nguyen
Abstract : Introduction: Surfing is a popular pastime in coastal areas around the world with increasing numbers of participants. There is a lack of detailed data in the literature regarding surfing-related head and neck (HN) injuries. Materials and Methods: We queried the National Electronic Injury Surveillance System (NEISS) database to characterize patient demographics, injury types, injury subsite, and emergency department (ED) disposition status associated with surfing-related HN injuries between 2009 and 2020 in the United States. Results: A total of 54, 978 estimated national cases were reported from 2009 to 2020. Injuries to the head (36.0%) and neck (35.8%) were most common. Young adults (ages 18–35) made up most ED visits, whereas older adults (>35) made up most (63.5%) admissions. Laceration (46.1%) was the most common injury among ED visits, whereas fracture (30.5%) and internal injury (29.2%) were most common in admitted patients. Concussions represented 7.5% of injuries overall, 9.1% of pediatric injuries, and 9.9% of young adult injuries. Conclusions: When treating a patient who presents with injury suffered during surfing, a thorough examination of the HN should be performed. Specific attention should be given to evaluation of lacerations, fractures, internal ear injuries, and concussions. Pediatric and young adult patients are at increased risk of concussion. The majority of surfing injuries can be treated in an outpatient context.